Identification of Candida lusitaniae as an opportunistic yeast in humans. - Holzschu, D L (1979)
Four yeast strains, causally associated with infection in a patient with acute myelogenous leukemia, were identified by standard methods currently used in yeast taxonomy as representatives of Candida lusitania van Uden et do Carmo-Sousa. Because this species has not been recognized previously as an opportunistic yeast in humans, molecular taxonomic methods were applied to confirm its identity. The nuclear deoxyribonucleic acid (DNA) base composition of two clinical isolates was shown to be 45.1 mol% guanine plus cytosine as compared to 44.7 mol% guanine plus cytosine for the type strain of this species. DNA/DNA reassociation experiments revealed more than 95% complementarity between the DNAs from the clinical isolates and that of the type strain of C. lusitaniae, thus confirming their classification by conventional taxonomy. A key is provided to differentiate C. lusitaniae from two phenotypically similar Candida species.